COGNITIVE AND PSYCHOLOGICAL-PEDAGOGICAL ASPECTS OF CROSS-CULTURAL EDUCATION (CREATIVITY OF POETS AND WRITERS OF KAZAKHSTAN OF THE XX CENTURY) - Кошербаев, Ренад (Pedagogy and Psychology, 2022)
The article explores the cognitive, psychological and pedagogical ideas of writers and poets of Kazakhstan at the beginning of the twentieth century. Feature of work done by B.G. Kairbekov, O. Suleimenov and G.K. Belger lies in the fact that they did not create them in their native language. Humane attitude to the development of different national languages in Kazakhstan is a fertile ground for the development of creativity. Therefore, Kazakh writers wrote free in Russian, and they said about G. Belger: "a German with a Kazakh soul." The Russian language as the language of interethnic communication was used in botheveryday life and in communication, whileother languages were actively developing. The work of poets and writers was an important indicator of ongoing cultural changes in democratic Kazakhstan. This, undoubtedly, was reflected in mental activity, cognition of creative personalities, testified to an extraordinary perception and intercultural approach. Examples of the works of such poets and writers give us an opportunity to explore the symbiosis of psychological and cognitive problems in the context of the modern paradigm of education